Philosophischer Monimus und christliche Theologie Philosophischer Monimus und christliche Theologie - Theunissen, Michael (Zeitschrift für Theologie und Kirche, 2005)
In philosophical monism, the One either includes or excludes the Many. From the standpoint of Christian theology however, it abstracts from the state of the world. The state of the world forces theology to accept a concept of God which cuts it off from the whole.